Coretax Effectiveness and MSME Tax Compliance: The Moderating Role of Tax Consultants - Rastia Yusranaditya; Herry Laksito (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2026)
This study aimed to examine the effect of Coretax effectiveness on Micro, Small, and Medium Enterprises (MSME) taxpayer compliance and analyze the moderating role of tax consultants in strengthening this relationship. This research applied a quantitative approach with an explanatory research design. Primary data were collected through questionnaires distributed to 382 MSME taxpayers in Semarang City and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results showed that Coretax effectiveness had a positive and significant effect on MSME taxpayer compliance, indicating that an effective digital taxation system improved taxpayers’ ability to fulfill their tax obligations. Furthermore, the role of tax consultants significantly strengthened the relationship between Coretax effectiveness and taxpayer compliance by assisting taxpayers in adapting to digital tax transformation. This study concluded that improving taxpayer compliance requires not only technological innovation but also professional support mechanisms. The limitation of this study was its focus on MSMEs in Semarang City; therefore, future studies are encouraged to expand the research scope. This study contributed to digital taxation literature by integrating the Technology Acceptance Model and Role Theory perspectives.